2013
DOI: 10.3109/10717544.2013.801047
|View full text |Cite
|
Sign up to set email alerts
|

In vivostudy of effects of artesunate nanoliposomes on human hepatocellular carcinoma xenografts in nude mice

Abstract: To investigate the effect of artesunate nanoliposomes on cultured cells in vitro and hepatocellular carcinoma xenografts in BALB/c-nu mice. Fluorescence polarization was applied for measurement of mitochondrial membrane fluidities; inhibition test of tumor cell proliferation in vitro was performed and nude mice xenograft model from human hepatocellular carcinoma (HCC) was established. Cytotoxicity of these compounds was evaluated by MTT assay on hepatocellular carcinoma xenografts in nude mice. Anisotropy (r-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…The antitumor effects of NLCs were investigated in gastric tumor-bearing BALB/c nude mice models (Jin et al, 2013). BALB/c mice were inoculating (s.c.) subcutaneously in the left armpit with SGC7901 cells suspended in PBS.…”
Section: In Vivo Antitumor Effectsmentioning
confidence: 99%
“…The antitumor effects of NLCs were investigated in gastric tumor-bearing BALB/c nude mice models (Jin et al, 2013). BALB/c mice were inoculating (s.c.) subcutaneously in the left armpit with SGC7901 cells suspended in PBS.…”
Section: In Vivo Antitumor Effectsmentioning
confidence: 99%
“…ART, as a potential cancer chemoprevention agent, has a potential anti-cancer effect on several kinds of tumors such as Kaposi’s sarcoma, hepatocellular carcinoma, and non-small cell lung cancer [17,18,19,20] and ART is recognized as a safe compound to treat malaria [24] Our experimental design provides a useful model for studying the effect and molecular mechanism of ART on bladder cancer and to our knowledge, this is the first time the therapeutic effect of ART on bladder cancer has been reported. There was no difference in weight among rats in each group (data not shown), which indicated that ART could inhibit tumor growth in the bladder cancer rat without any side effects on weight maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there is increasing evidence that ART has anti-cancer capability [16]; ART has been shown to have a profound cytotoxic action against several tumors, such as Kaposi’s sarcoma, hepatocellular carcinoma, non-small cell lung cancer and cervical cancer [17,18,19,20]. However, whether ART can inhibit the growth of bladder cancer has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Artesunate is particularly active against cytomegalovirus that are resistant to DNA polymerase inhibitors like valganciclovir [23, 24]. Artesunate has demonstrated empirical cytotoxicity against a variety of cancer cells [general review- 22, specific examples: lymphoma and myeloma, 25; pancreatic, 26; hepatocellular, 27; osteosarcoma, 28; gastric, 29; leukemia, 30, 31; glioma, 32]. …”
Section: Introductionmentioning
confidence: 99%